Navigating urban climate design implementation challenges: insights from Brisbane's built environment experts - Liu, YiSong; Guaralda, Mirko; Yigitcanlar, Tan; Limb, Mark; Garcia-Hansen, Veronica (Journal of urban design, 2025)
Urban densification, intended to enhance efficiency, often exacerbates urban climate issues like diminished thermal and wind comfort. Despite substantial evidence on the climatic impacts of urbanization, integrating this knowledge into development practices remains difficult. This study investigates urban climate design in Brisbane, Australia through semi-structured interviews with built environment professionals. A qualitative thematic analysis uncovers several challenges: ambiguous planning codes, a knowledge gap on microclimate effects, short-term political and economic priorities, and a lack of robust technical methods in early design stages. Recommendations include technological development, raising public awareness, and incorporating climate-sensitive practices in urban planning and design.